Treatment for a B-cell acute lymphoblastic leukemia patient carrying a rare TP53 c.C275T mutation: A case report - Wang, Runan; Wang, Wenliang; Liu, Xuan; Wang, Huan; Zhang, Bin; Li, Shuang; Zhang, Haining; Yang, Jiawei; Zhao, Jishun; He, Qiuying; Zhang, Jihong; Liu, Danping; et al. (Frontiers in Oncology, 2023)
TP53 mutations have been associated with poor prognosis in the vast majority of cancers. In this study, we present a pediatric B-cell acute lymphoblastic leukemia (B-ALL) patient carrying a rare TP53 c.C275T mutation. This extremely rare mutation affects an amino acid residue located between the TAD domain and the DNA binding domain of TP53. The patient was resistant to most conventional chemotherapy regimens as she remained minimal residual disease (MRD)-positive after 5 rounds of such regimens. We tested the sensitivity of the patient's leukemic cells to 21 anti-cancer drugs by performing in vitro drug sensitivity assays. The results showed that bortezomib had a very strong killing effect on the patient’s leukemic cells. Therefore, we subsequently treated the patient with bortezomib combined with vindesine, cytarabine, and fludarabine. After one course of treatment, the patient became MRD-negative and there was no recurrence during a 9-month follow-up. In conclusion, our report suggests that the TP53 c.C275T mutation is associated with poor prognosis of ALL because our patient with this mutation was resistant to conventional chemotherapy regimens. Fortunately, bortezomib combined with chemotherapy could achieve better therapeutic effect in this type of ALL.